Picture Archiving and Communication Systems (PACS) as a Solution to Inequality in the Number of Radiological Resources in West Java - Barasabha, Thareq; Hardiyanti, Yati (International Journal of Radiology and Imaging, 2022)
Inequality of health care facilities, especially radiology resources, occurs in West Java Province. There are many class A hospitals in provincial capitals, while in areas far from the provincial capital and from DKI Jakarta Province, the quantity and quality of hospitals are still lacking. Likewise with the quantity of radio diagnostic instruments and human resources. 12 radiology specialists and an additional 192 radiographers are needed in West Java Province. Archiving and image communication systems (PACS) can be used as a solution so that health workers in hospitals located far from the city or district centers can consult, and expert conclusions can be obtained from radiology specialists at referral centers. Keywords: PACS, radio diagnostic, radiology specialist, radiographer, West Java